Technological Model and Sustainable Rural Development for Rainy-Spell Corn Producers in Mexico - Damian-Huato, Miguel A.; Cruz-Leon, Artemio; Ramirez-Valverde, Benito; Aragon-Garcia, Agustin; Ramirez-Carrasco, A. Patricia; Lopez-Olguin, Jesus F. (IntechOpen, 2012)
None